VISUAL OUTCOME OF PAEDIATRIC TRAUMATIC CATARACT IN PAEDIATRIC OPHTHALMOLOGY DEPARTMENT OF A TERTIARY CARE HOSPITAL - Chaudhry, Rabia Khawar; Rehman, Aziz ur; Muhammad Nasar Qamar Khan; Dad, Mehboob; Kazi, Ghulam Qadir (Journal of Ayub Medical College Abbottabad, 2022)
Background: Paediatric traumatic cataract is one of leading treatable cause of childhood blindness. The purpose of this study is to analyse number of avoidable blindness in children and to access final visual outcomes, causative factors, strategies for the prevention and management. Methods: One hundred and twenty patients of ocular traumatic cataract age between 2 months to 14 years were treated in Department of Paediatric Ophthalmology from April 2019 till April 2020wasprospectivelyreviewed. Data included age, gender, time of presentation, type of injury, anterior segment with fundus examination, time and type of surgery, visual outcome at presentation and final visual outcome. Visual acuity was assessed by fixation and following, Snellen’s chart according to patient’s age. Some patients underwent for lens aspiration and rest underwent for lens aspiration, posterior capsulotomy and anterior vitrectomy followed by intraocular lens implantation under general anaesthesia. Patients who lost follow ups for two months were not included in study. Analysis of data was done using SPSS for window version 24.0. Results: One hundred and twenty eyes operated for traumatic cataract among which 64 (53.34%) patients were males and 56 (46.66%) were females. The average age of patients was 7.8 years with traumatic cataract. Initial Uncorrected visual out come at the time of presentation ranged from 6/60 to light perception. 15 %of children with traumatic cataract had post-operative final visual outcome of better than 6/18. Conclusion: The commonest cause of ocular injuries in our pediatric ophthalmology department was domestic, mostly in 5-9 years of age with greater number in males. In traumatic cataract extraction final visual outcome depends on initial visual outcome, source and type of injury, duration of presentation, duration of surgery and complications.